PROVIDING AN APPLIED MODEL FOR ALIGNING HUMAN RESOURCE STRATEGIES WITH THE CORPORATE STRATEGIES OF CUSTOMS IN IRAN TO IMPROVE THE PERFORMANCE - Rezaeian, Mohammad; Salajegheh, Sanjar; Sayadi, Saeed (Revista Inclusiones, 2019)
The aim of the present study is to propose a functional model for aligning HR strategies with grand strategies to improve performance of customs procedures in Iran. The research type was "applieddevelopmental" in terms of purpose, and "descriptive-analytical survey" in terms of methodology. Both library and field studies were used for data collection. The statistical population consisted of 50 faculty experts with a Ph.D. in management and senior experts from Islamic Republic of Iran Customs Administration. According to Krejcie and Morgan table, the sample size was determined to be 44, and samples were selected using simple random sampling method. A researcher-made questionnaire was used to collect data. In order to identify HR strategies aligned with the grand strategy, SWOT matrix was used for strategy formulation. First, a binomial test was run to identify the strengths, weaknesses, opportunities, and threats affecting the alignment of HR strategies with grand strategy. Then, the importance of factors was determined using pairwise comparison via AHP software. HR strategy of Islamic Republic of Iran Customs Administration was placed in “SO” zone, i.e. superiority of opportunities and strengths. Therefore, HR strategy was aligned with grand strategy. Student’s t-test was used analyze HR strategy, grand strategy performance.